2023
DOI: 10.3390/biomedicines11071845
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Metabolomics in Diet–Breast Cancer Relations: Current Research, Challenges, and Future Directions—A Review

Farhad Vahid,
Kimia Hajizadeghan,
Adeleh Khodabakhshi

Abstract: Breast cancer is one of the most common types of cancer in women worldwide, and its incidence is increasing. Diet has been identified as a modifiable risk factor for breast cancer, but the complex interplay between diet, metabolism, and cancer development is not fully understood. Nutritional metabolomics is a rapidly evolving field that can provide insights into the metabolic changes associated with dietary factors and their impact on breast cancer risk. The review’s objective is to provide a comprehensive ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 205 publications
(252 reference statements)
0
1
0
Order By: Relevance
“…Parabens (MP, EP, PP, BP) earlier BC development [135], potent carcinogens [121] mimic of endogenous hormones, interact with signaling transduction pathways, such as HER2 signaling, modulate of key enzymes involved in estrogen metabolism, increase pro-oncogenic c-Myc expression in ER+/HER2+ BC cells, promote EMT [135] BC and non-malignant cell lines [121] RT-qPCR, WB [121] Polychlorinated biphenyls (PCBs) increased BCR [136] as EDC [137], enhance metastatic proprieties of BC cells by activating ROCK, increase cell motility/migration/invasion, disease progression, induce the intracellular ROS production [138] human BC cell lines, animal models [138], mice mammary organoid cultures [125] LC-MS/MS [125] Dioxins and dioxin-like chemicals (TCDD) controversially role: positive association between airborne dioxins and invasive BCR [139]; no increased BCR for long-term airborne dioxins [140]; no association between dietary dioxin and BCR [141]; significant positive association between dioxin exposure and BCR [142]; protective effect against BC [143] disruption of the CXCL12/CXCR4 axis limits the metastasis of BC cells to the lung in mice [143]; BC cells may acquire pro-metastatic and CSCs features [144] BC cell lines [143], co-culture model using MCF7 and MDA-MB-231 BC cell lines together with hMADS preadipocytes and in vivo Zebrafish larvae model [144] gene chip microarray, RT-PCR, FC [143], nLC-MS/MS, qRT-PCR, Zebrafish larva metastasis assays [144] Dietary factors [145] Omics: nutrigenomics and nutriproteomics [102], nutritional epigenomics/epitranscriptomics, and epiproteomics [104], phosphoproteomics [146], metabolomics/nutritional metabolomics [103,145,146] High fructose intake PT [147,148], fructose-induced carcinogenesis…”
Section: Methods For Biomarkers Investigationmentioning
confidence: 99%
See 1 more Smart Citation
“…Parabens (MP, EP, PP, BP) earlier BC development [135], potent carcinogens [121] mimic of endogenous hormones, interact with signaling transduction pathways, such as HER2 signaling, modulate of key enzymes involved in estrogen metabolism, increase pro-oncogenic c-Myc expression in ER+/HER2+ BC cells, promote EMT [135] BC and non-malignant cell lines [121] RT-qPCR, WB [121] Polychlorinated biphenyls (PCBs) increased BCR [136] as EDC [137], enhance metastatic proprieties of BC cells by activating ROCK, increase cell motility/migration/invasion, disease progression, induce the intracellular ROS production [138] human BC cell lines, animal models [138], mice mammary organoid cultures [125] LC-MS/MS [125] Dioxins and dioxin-like chemicals (TCDD) controversially role: positive association between airborne dioxins and invasive BCR [139]; no increased BCR for long-term airborne dioxins [140]; no association between dietary dioxin and BCR [141]; significant positive association between dioxin exposure and BCR [142]; protective effect against BC [143] disruption of the CXCL12/CXCR4 axis limits the metastasis of BC cells to the lung in mice [143]; BC cells may acquire pro-metastatic and CSCs features [144] BC cell lines [143], co-culture model using MCF7 and MDA-MB-231 BC cell lines together with hMADS preadipocytes and in vivo Zebrafish larvae model [144] gene chip microarray, RT-PCR, FC [143], nLC-MS/MS, qRT-PCR, Zebrafish larva metastasis assays [144] Dietary factors [145] Omics: nutrigenomics and nutriproteomics [102], nutritional epigenomics/epitranscriptomics, and epiproteomics [104], phosphoproteomics [146], metabolomics/nutritional metabolomics [103,145,146] High fructose intake PT [147,148], fructose-induced carcinogenesis…”
Section: Methods For Biomarkers Investigationmentioning
confidence: 99%
“…Sellami et al (2020) showed that nutrigenomics and nutriproteomics are recently developed omics fields that are focused on the interaction between nutrients and human genome/proteome in order to decipher the role of dietary factors in carcinogenesis [102]. Additionally, Vahid et al (2023) revealed that nutritional metabolomics is a rapidly evolving field developed as an interplay between dietary factors, metabolic changes, and breast carcinogenesis or breast cancer risk (BCR) [103]. Nutritional epigenomics/epitranscriptomics/epiproteomics are focused on the influence of nutrients and bioactive dietary components on cytosine methylation, histone PTMs and specific RNA molecules as main epigenetic factors involved in BC development [104].…”
Section: Bc Is An Ecological/environmental Disordermentioning
confidence: 99%
“…Importantly, metabolomics, the study of chemical metabolites derived from metabolic processes "offers an opportunity to develop a biomarker-based approach to dietary assessment in cancer epidemiology" [21]. A 2023 review of nutritional metabolomics in the association of diet and breast cancer described a wide variety of metabolites from fat, protein, carbohydrate, and other nutrients, but significantly, no mention was made of metabolites related to dietary phosphate [22]. Yet, circulating serum Pi derived from dietary phosphorus absorbed in the intestines "functions as a constituent of cellular metabolites" [23].…”
Section: Diet and Cancermentioning
confidence: 99%